Diagnosis of education programs in sustainable consumption and market green policy sustainable production capital district (2018)
(Eng) This article contains the results of Diagnosis of Education Programs in Sustainable Consumption and Green Marketing Promotion Strategy for Sustainable Consumption Policy Sustainable Production Capital District (1) for the corporate sector was developed. The diagnosis allowed noting from the priority actions proposed in the Action Plan 2004 Policy for Sustainable Production Capital District was compliance with the Education Program Sustainable consumption but not for Green Markets Programme, although there are other actions that enable identification of related results. In turn, the development of indicators in the medium and long term programs to publicize the Policy on Sustainable Production from the Capital District Environmental Business Management Program (2), and the promotion of the culture of the Sustainable Consumption and Markets suggests greens.